Waqf development and innovation : socio-economic and legal perspectives - Ali, Syed Nazim; Oseni, Umar A. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Waqf is one of the most potent socio-economic tools for reducing public sector deficit and break the chain of intergenerational poverty. Providing a high-level discussion on waqf development and innovation within the context of the modern socio-economic and legal developments, this book examines the importance and potentials of waqf and the issues relating to its legal and regulatory framework. The research delivers future directions for countries that plan to explore this socio-economic institution. Readers and policymakers will be able to replicate successful experiments and learn from some failed initiatives to seek alternative funding platforms to support the fiscal policies of developing countries. The volume discusses the relevance and novel application of waqf in the modern economic system and social development, it reviews applicable laws and regulation pertaining to waqf and trust laws and examines critical, cross-country case studies and experiences. Setting an agenda for further researchers in the fields of waqf, this comprehensive high-level analysis with case studies from leading jurisdictions across the world, is a key resource for researchers, policymakers and institutions interested in charitable endowments, Islamic finance, and social finance"--
OCLC-licensed vendor bibliographic record.
Keywords: Charities -- Developing countries; Economic assistance -- Developing countries; Debts, Public -- Developing countries; Endowments -- Religious aspects -- Islam; BUSINESS & ECONOMICS / Accounting / Financial; BUSINESS & ECONOMICS / Finance